QUALITATIVE COMPARISON OF LOCALLY PREPARED 99mTc-LABELED METHYLENE DIPHOSPHONATE AND 99mTc-LABELED PYROPHOSPHATE - Mehmood, R.; Sajid, K. M.; Sabih, Durr- e-; Iqbal, A. (The Nucleus, 2020)
Different parameters affecting labeling of 99mTc with two compounds were studied in order to standardize the procedure for the preparation of 99mTc -MDP and 99mTc -PYP. Briefly radiochemical purity, stability, pyrogenicity were studied. Radiochemical purity was checked by paper chromatography. Stability was checked by incubating the labeled products for several hours at room temperature. Pyrogenicity was checked by noting the rectal temperatures after injection of the preparation into the rabbit. The optimized preparations were then injected to the rabbits to compare imaging quality and biodistribution of the agents in the body. Finally the preparations were injected into patients to see the image quality and diagnostic efficacy of the technique. The results show superior image quality and biodistribution with locally prepared 99mTc-MDP as compared to 99mTc-PYP although both the preparations were having good radiochemical purity and stability. It is concluded that the locally developed techniques for preparation of 99mTc-MDP and 99mTc-PYP are simple, safe and of acceptable quality. The data on biodistribution in these bone agents suggests relatively good target to non-target contrast with 99mTc-MDP. The image quality with patient scans is also superior with 99mTc-MDP. This confirms that the homemade 99mTc-MDP is superior in quality than 99mTc-PYP. This is in agreement with the previous findings.